Analysis of Investment Policy in Indonesia After the Ratification of the Protocol To Amend The Asean Comprehensive Investment Agreement - Poly Pagna; Dewa Putu Mantera; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum, Universitas Warmadewa, 2019)
The Government of Indonesia in an effort to increase Foreign Direct Investment (FDI) and increase trade between ASEAN member countries (intra-ASEAN Trade) ratified the protocol to amend the asean comprehensive investment agreement in the form of Presidential Regulation of the Republic of Indonesia Number 92 of 2015. Constrained by regulations concerning legalization and licensing at the center and in the area of accelerating efforts, the Investment Coordinating Board is given the task of coordinating the implementation of policies. Moving on from that, the problem was formulated regarding how the substance and investment policies in Indonesia after the ratification of the protocol to amend the asean comprehensive investment agreement. The substance of the protocol to amend the ASEAN comprehensive investment agreement is to create a free and open investment regime in ASEAN, through investment regimes, increased protection, increased transparency and predictability of rules, with fair competition and non-discrimination treatment. With the transition from the existence of the understanding of liberalism, efforts must be made to strengthen the family principle in accordance with Article 33 paragraph (1) of the Constitution. Globalization should be harmonized by considering the entire foundation and a material study of the academic community with the aim of defending the nation's ideology. Then the application of the Triple Helix concept as a transformation effort.